2005
DOI: 10.1152/ajpheart.01157.2004
|View full text |Cite
|
Sign up to set email alerts
|

Role of adenosine A1 and A3 receptors in regulation of cardiomyocyte homeostasis after mitochondrial respiratory chain injury

Abstract: of adenosine A 1 and A3 receptors in regulation of cardiomyocyte homeostasis after mitochondrial respiratory chain injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…The A 3 AR couples to classical second-messenger pathways such as inhibition of adenylyl cyclase 24 , stimulation of PLC 25 and calcium mobilization [26][27][28][29] . In cardiac cells, A 3 AR agonists induce protection through the activation of K ATP channels 30 .…”
Section: Ar Signalling Pathways and Regulationmentioning
confidence: 99%
“…The A 3 AR couples to classical second-messenger pathways such as inhibition of adenylyl cyclase 24 , stimulation of PLC 25 and calcium mobilization [26][27][28][29] . In cardiac cells, A 3 AR agonists induce protection through the activation of K ATP channels 30 .…”
Section: Ar Signalling Pathways and Regulationmentioning
confidence: 99%
“…ARTICLE AR subtype of all of the compounds (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) reported in this work.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 97%
“…Interest for this new series was driven by the structural similarity between the PHTZ skeleton and both the 2-aryl-1,2,4-triazolo [4,3-a]quinoxalin-1-one (TQX) and the 4-carboxamido-quinazoline (QZ) scaffolds extensively investigated in our previously reported studies. Our attention was focused at position 4 of the phthalazine nucleus where different amido and ureido moieties were introduced (compounds [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Some of the new PHTZ compounds showed high hA 3 AR affinity and selectivity, the 2,5-dimethoxyphenylphthalazin-1(2H)-one 18 being the most potent and selective hA 3 AR antagonist among this series (K i = 0.776 nM; hA 1 / hA 3 and hA 2A /hA 3 > 12000).…”
Section: ' Introductionmentioning
confidence: 99%
“…The highly specific agonist, CF101, (generically named IB-MECA) downregulates expression levels of the Fas receptor and TNF-α, preventing apoptosis in liver cells derived from mice with concanavalin A-induced inflammation (21). In addition, it was found that treatment with A 3 AR agonists protects from and prevents apoptosis in normal cells, including liver and heart cells, cerebral ischemia and myelotoxicity (3,(22)(23)(24)(25)(26).…”
Section: Rationale For the Treatment Of Glaucoma With A 3 Ar Agonistsmentioning
confidence: 99%
“…High expression of A 3 AR was found in the non-pigmented ciliary epithelium of pseudoexfoliation eyes, with and without glaucoma, compared with normal and glaucomatous control eyes. In addition, significant upregulation of A 3 AR induced hypoxia and oxidative stress in non-pigmented epithelial cells (26,29). RGCs were also shown to express A 3 AR mRNA (30).…”
Section: Rationale For the Treatment Of Glaucoma With A 3 Ar Agonistsmentioning
confidence: 99%